Pengembangan Desain Kurikulum Pendidikan Agama Islam Berpusat pada Mata Pelajaran - Ridha Aulia Ridha; Fathunnajih (Islah Tarbawi: Journal of Islamic Education and Learning, 2025)
This article discusses the importance of developing the Islamic Religious Education (PAI) curriculum that focuses on subject matter to shape students’ character and moral values, in line with the goals of national education. This study employs a qualitative approach using the library research method. The data analysis technique used is content analysis of various relevant literatures concerning the design of the PAI curriculum. The findings indicate that the development of the PAI curriculum must consider the principles of relevance, continuity, flexibility, efficiency, and effectiveness in order to respond to the dynamic needs of society. The study also identifies several challenges in its implementation, such as limited teacher mastery of the subject matter, the lack of appropriate teaching methods, and insufficient supporting facilities and infrastructure. The article recommends the need for collaboration among the government, schools, and the community to realize an effective PAI curriculum. With the right approach and synergistic support, the curriculum is expected to produce a generation that is religious, morally upright, and prepared to face global challenges.